SYIAH DAN TAFSIR AL-QUR’AN (Telaah Awal Ayat-Ayat Jihad Dan Nikah Mut’ah) - Al Amin, Hulaimi; Ridho, Abdul Rasyid (el-Umdah, 2022)
This article discusses the approach of Qur'anic interpretation in the Shia tradition which is also widely practiced by their scholars. The aim is to find out the approaches carried out by the Shia group with regard to the interpretation of the Qur'an. The object of research in this article is the verses related to jihad and mut'ah marriage. By using descriptive analytical method, the author concludes that; First, Shia is a group that is concerned with the Qur'an and is no different from other groups. Second, in terms of interpretation, in the author's opinion, the approach of this group in interpreting the verses of the Qur'an is to consider the context, situation and conditions surrounding the Qur'an. In other words, their approach can be included in the contextual approach. This can be seen from some of their interpretations such as jihad and mut'ah marriage.